Anti-Microbial Resistance in Global Perspective - Ackers, Louise. author. aut Link
XX, 191 p. 18 illus., 14 illus. in color.
Keywords: ‘The Maternal Sepsis Intervention has had a profound impact on maternal mortality and antibiotic use whilst also reducing hospital costs. The Ministry of Health is keen to explore opportunities to extending the lessons learnt and integrate them in national policy-making.' -Dr. Richard Mugahi, Ministry of Health, Uganda. This open access book provides an accessible introduction to the mechanics of international development and global health text for policy-makers and students across a wide range of disciplines. Antimicrobial resistance is a major threat to the well-being of patients and health systems the world over. In fragile health systems so challenged, on a day-today basis, by the overwhelming burden of both infectious and non-communicable disease, it is easy to overlook the impacts of AMR. The Maternal Sepsis Intervention, focusing on a primary cause of maternal death in Uganda, demonstrates the systemic nature of AMR and the gains that can be made through improved InfectionPrevention Control and direct engagement of laboratory testing in antibiotic prescribing. Louise Ackers holds a Chair in Global Social Justice at the University of Salford, UK, and has recently been appointed as a consultant for the World Health Organization. Gavin Ackers-Johnson is Researcher at the University of Salford, UK. Joanne Welsh is Researcher at the University of Salford, UK. Samuel Opio is Secretary General of the Pharmaceutical Society of Uganda. Daniel Kibombo is a Microbiologist at Fort Portal Regional Referral Hospital and the Infectious Disease Institute.